IMF Survey, Volume 35, Issue 13. (IMF Survey; IMF Survey ;, 2006)
Afghanistan: IMF loan; de Rato, African Governors meet; Bank-Fund collaboration; New Zealand, Libya; Chinese monetary policy; Lebanon: reconstruction; Canada: commodity boom; Persian Gulf: statistical agency; ECB monetary policy; WAEMU; Mineral resources.